CMA1 is potent prognostic marker and associates with immune infiltration in gastric cancer - Shanping Shi; Shazhou Ye; Jianmei Mao; Yuqing Ru; Yicong Lu; Xiaoyue Wu; Mingjun Xu; Tingwei Zhu; Yibo Wang; Yuanming Chen; Xiaoli Tang; Yang Xi (Taylor & Francis Group, 2020)
Background: Chymase 1 (CMA1), a gene known to be expressed in mast cells (MCs), is largely linked to immunity. However, the relationship between CMA1 and prognosis of multiple tumours and tumour-infiltrating lymphocytes (TILs) remains elusive. Methods: The differential expressions of CMA1 in different tumours and their corresponding normal tissues were evaluated via exploring Tumour Immune Estimation Resource (TIMER) and Oncomine database; the correlation within expression level of CMA1 and outcome of cancer patients was evaluated via Kaplan-Meier plotter and Gene Expression Profiling Interactive Analysis (GEPIA) database; the correlation between CMA1 and tumour immune cell infiltration was further investigated by TIMER; additionally, the correlation between CMA1 and gene signature pattern of immune infiltration were checked using TIMER and GEPIA. Results: There were significant differences in CMA1 expression levels between gastric cancer (GC) tissues and adjacent normal tissues. The high expression of CMA1 was closed related to poor overall survival (OS) and progression-free survival (PFS) in patients with GC (OS HR = 1.50, p = .00015; PFS HR = 1.33, p = .016). Especially, in GC patients at N1, N2 and N3 stages, high CMA1 expression was correlated with poor OS and PFS, but not with NO (p = .15, .09). The expression of CMA1 was positively associated with the levels of infiltrated CD4+, CD8+ T cells, neutrophils, macrophages, and dendritic cells (DCs) in GC. Whereas, CMA1 expression was considerably associated with various immune markers. Conclusion: CMA1 is a key gene whose expression level is significantly correlated with GC prognosis and infiltration levels of CD8+, CD4+ T cells, neutrophils, macrophages, and DCs in GC. In addition, the expression of CMA1 may be involved in regulating tumour-associated macrophages (TAMs), dendritic cells, exhausted T cells and regulatory T cells in GC. It suggests that CMA1 could be utilized as a prognostic marker and a sign of immune infiltration in GC.